Ticks (Acari: Argasidae, Ixodidae) from Middle and pre-Hispanic Late Holocene associated with human activities in northwestern Argentina - Nava, Santiago; Martinez, Jorge Gabriel; Arreguez, Guillermo Anibal; Guglielmone, Alberto (2018)
One male of Amblyomma parvitarsum and one male and a female of Ornithodoros sp. were recovered from archaeological layers of the Middle Holocene in a rock shelter in the province of Catamarca, used by hunter-gatherer groups. Another two ticks identified as a female and a nymph of Argas cf. neghmei were recovered from a layer of the Late Holocene in other rock shelter in the province of Tucumán used by humans of agro-pastoral complex societies previous to the Hispanic invasion. The presence of Amblyomma parvitarsum is probably related to hunting activity, while Ornithodoros sp. was probably an opportunistic parasite established in the shelter. Argas cf. neghmei was probably a parasite of birds as is A. neghmei, a tick that has been found in the nests of birds, chicken houses, but also in human dwellings. The presence of A. cf. neghmei may originate from birds naturally breeding in the shelter or from the nests of birds introduced into the shelter by humans.